THE IMPORTANCE OF PLANNING, ADMINISTRATION AND ORGANIZATION IN THE ESTABLISHMENT AND EXPANSION OF FOOD HYGIENE SERVICES - H. Neshat (Tehran University of Medical Sciences, 1972)
Since in the last decade, tremendous progress has been achieved in developed countries in all branches of technology including food technology, such to new ideas and techniques should be partially conveyed to the developing countries to create closer relationship between these two sectors of the world. The preventive measures should be seriously taken to avoid the food poisoning outbreak which usually happens through contamination of foods and distribution of such foods by quickest contact (Jet food borne diseases). Food hygiene is a multidisciplinary science in which different scientific discipline is involved and the problem within the subject would be of nationa1, regional on international interest. The organization and management of food hygiene program in each country should be based upon the socio-economic development of the country and the direct complete imitation of such a program of a developed country in a developing country is not always successful. The Lab/field relationship should be strengthened in an adequate food hygiene program as a safeguard of Public health. Food Hygiene specialists are recently defined by WHO expert committee on food hygiene as fol1ows.1. General Food Hygienists: Those who have graduate study on biochemistry, anatomy and physiology of animals, animal pathology, microbiology etc.2. Special Food Hygienists: Who have passed post-graduate courses and are specialized either by the type of foods, as specialist in fish, milk meat, etc., or by the scientific disciplines as food chemist, food microbiologist, food virologist, etc.3. Technician and Auxiliaries: Those who are trained for two years are called technicians. For Auxiliaries 9 months courses should be recommended.